Diskursus Rukyat: Metode Mengilmiahkan Kebenaran Hisab Awal Bulan Kamariah - Saputra s, Sadri; Wakia, Nurul (ELFALAKY: Jurnal Ilmu Falak, 2020)
AbstractHisab (theory) and rukyat (practice) are two methods of determining the beginning of the month qomariyah which each has a foundation in the Qur'an and Hadith, it shows that these two methods have a basis for then be used as a guide in determining the beginning of the month qomariyah, but the problem that arises of course is the criteria between these two different methods that cause differences in the community, but if observed in the implementation of these two methods, of course need each other, where the method of calculation asab theory-based theory must be proved scholarship, to prove the motive scholarship it takes the rukyat method as the only way to prove the truth of hisab, because the method of rukyat as a hilal observation step directly in the field. Likewise with the method of rukyat as a method oriented to the observation of hilal directly requires the method of reckoning as one of the ways to facilitate perukyat know the position of the new moon will be seen at the time of observation, he wrote in this paper, the author tries to unify the method of hisab and rukyat in the perspective of proof scientific.  Keywords: Hisab Method, Rukyat Method, Early Moon Qomariyah, Scientific